2020
DOI: 10.1038/s41598-020-63416-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between olfactory function and inhibition of emotional competing distractors in major depressive disorder

Abstract: We aimed to investigate the changes of olfaction of major depressive disorder (MDD) before and after medical treatment, and to preliminarily scrutinize the association between the olfactory function and the severity of depressive symptoms, response inhibition, and emotional responding. Forty-eight medicine-naïve MDD patients plus 33 healthy controls (HC) matched on gender, ages, and level of education, were recruited in the test group. The Chinese Smell Identification Test (CSIT), Self-reported Olfactory Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Our results also show pathway enrichment in sensory perception of the chemical stimulus, such as smell. This is consistent with evidence showing the correlation between smell and taste alterations in older MDD patients [80]. However, no study so far focuses on the roles of smell perception in insomnia.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also show pathway enrichment in sensory perception of the chemical stimulus, such as smell. This is consistent with evidence showing the correlation between smell and taste alterations in older MDD patients [80]. However, no study so far focuses on the roles of smell perception in insomnia.…”
Section: Discussionsupporting
confidence: 90%
“…Curiously, it has been recently demonstrated that both anxiety- and depression-like states lead to marked olfactory deficits along with impaired adult neurogenesis [ 18 ]. Indeed, the SVZ-derived neural progenitors migrate towards the olfactory bulb, where they differentiate into local neurons involved in olfactory system [ 62 ], while an association between olfactory function and depression has also been revealed [ 63 ]. In this regard, it was recently proposed that the rejuvenation of SVZ neurogenesis would be a promising strategy to arrest aging and come to resemble a youthful and health brain [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that thalamus and the prefrontal cortex shared one upregulated pathway involved in olfactory transduction. Indeed, olfactory transduction pathway has been associated with suicide ideation 68,69 .…”
Section: Discussionmentioning
confidence: 99%